Firms' performance and board size: A simultaneous approach in the European and American contexts. Issue 13 (28th July 2020) - Augusto, Mário; Pascoal, Rui; Reis, Pedro
ABSTRACT: The relation between performance and board size (BS) is analysed in the American and European contexts. It is found that return on assets (ROA) depends on BS defined as an endogenous explanatory variable. This potentially non-monotonous effect is modelled by introducing firm size and number of segments by board member as explanatory variables for ROA. BS net effect after accounting for the indirect effect resulting from these variables is negative. Differences in the results obtained for Tobin's Q, strategic investors' weight and equity to total assets, between America and Europe, suggest a more preventive management control in Europe.